FORMATION OF RESPONSIBLE ATTITUDE OF STUDENTS TO LEARNING AS A COMPONENT OF PROFESSIONAL TRAINING FUTURE PRIMARY SCHOOL TEACHERS - Kovshar О.В. (Pedagogy of Higher and Secondary Education, 2022)
In the article problems of the responsible attitude to training schoolboys at modern schools are considered, and problems of professional becoming of the future teachers of an elementary school are shown. Results of peda gogical eperiment are shown.